Maternal and Perinatal Outcomes in Women with Polycystic Ovary Syndrome Undergoing Artificial Frozen-Thawed Embryo Transfer Cycles: A Retrospective Study - Saeideh Dashti; Maryam Eftekhar; Danial Sarikhani; Nasim Tabibnejad (Advanced Biomedical Research)
Background: Polycystic ovary syndrome (PCOS) is a worldwide endocrine disorder of reproductive-aged women. In addition to infertility, PCOS may lead to unfavorable maternal and prenatal outcomes in assisted reproductive technology cycles. The aim of the study was to investigate the risk of adverse maternal and perinatal outcomes using frozen-thawed embryo transfer (FET) among women with and without PCOS. Materials and Methods: The data of 1064 women in the PCOS group and 1473 women in the control group were analyzed after FET. Adverse maternal and prenatal outcomes including gestational diabetes mellitus, pre-eclampsia, premature rupture of membranes, preterm birth, low birth weight, and stillbirth were compared between the two groups. Results: We did not find significant differences in the above-mentioned variables between the two groups. Gestational diabetes (7.1% vs. 11%), pre-eclampsia (12% vs. 11.8%), premature rupture of membranes (3.8% vs. 6.5%), preterm birth (13% vs. 15.9%), and low birth weight (10.9% vs. 14.7%) between PCOS and non-PCOS groups, respectively (P > 0.05). Conclusions: Our result showed that there are no differences between PCOS and non-PCOS women undergoing FET regarding maternal and neonatal outcomes.